Six Leadership Transformation Styles for Village Heads in Muslim Communities - Maulana, Ridho; Dikusuma Mardiana, Puja; Khoiriah, Khoiriah; Busmayaril, Busmayaril; Ohira, Norman (Al-Ashri: Ilmu-Ilmu Keislaman, 2024)
The research aims to find out the communication patterns of village heads among Muslim communities in Indonesia. This research uses a qualitative method with an ethnographic type, data sources were taken through in-depth interviews with ten informants who were selected using a proportional sampling technique. Apart from interviews, data was also taken by direct observation, and document analysis was even carried out regarding the data required according to the research objectives. All data was analyzed using techniques analysis interactive Miles and Huberman's. Research findings found six leadership styles of Village Heads in Muslim communities, these six styles are i) exploring the potential of local communities, ii) conducting regular evaluations, iii) conducting deliberations with stakeholders, iv) analyzing the needs of the community, v) conducting surveys of the community regarding the performance that has been carried out and vi) improving performance from the evaluation results. The leadership style that the Village Head has implemented in this research has impacted increasing the Muslim community's participation in holistically developing the village, both from religious, economic, social and cultural aspects.